Dry battery diaphragm paper and preparation method thereof

By using a combination of composite fiber paper and reinforced slurry in dry battery separator paper, the problem of insufficient porosity and liquid absorption of existing separator paper is solved, the tensile strength and thermal insulation performance of separator paper are improved, and the battery is enhanced Safety and performance stability.

CN119208904AActive Publication Date: 2024-12-27DONGGUAN SOGNUO NEW MATERIALS CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411491295.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2024-12-27
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The porosity, liquid absorption and specific surface energy of existing dry battery separators are low, resulting in short-circuiting of positive and negative electrodes of the battery, affecting battery safety, and lacking thermal insulation performance, making it difficult to automatically close in abnormal situations to prevent short-circuiting and overheating. .

Method used

Using dry battery separator paper composed of composite fiber paper and reinforced slurry, composite fiber paper synthesizes functionalized dioxide through materials such as γ-aminopropyltriethoxysilane, ethyl orthosilicate, thiopropyltrimethoxysilane and other materials. Silicon, blended with polypropylene fiber, aramid fiber, and polyester fiber, added with modified aerogel to form a separator paper with high porosity and high alkali absorption rate, and coated with silicon carbide nanowhiskers and oxidation on the surface Aluminum reinforces fillers to improve tensile strength and thermal insulation properties.

Benefits of technology

The high porosity, high alkali absorption rate and excellent tensile strength of the diaphragm paper are achieved, reducing the risk of battery short circuit and overheating, and improving the safety performance and performance stability of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005100129600000111
    Figure BDA0005100129600000111
  • Figure BDA0005100129600000121
    Figure BDA0005100129600000121
Patent Text Reader

Abstract

The invention relates to the technical field of diaphragm paper, and discloses dry battery diaphragm paper and a preparation method thereof. The prepared dry battery diaphragm paper is composed of the composite fiber paper and the reinforcing slurry coated on the surface of the composite fiber paper. The diaphragm paper has the advantages of excellent strength, high porosity, high alkali absorption rate, good wettability and the like; in the composite fiber paper, composite fibers formed by blending polypropylene fibers, aramid fibers and polyester fibers are adopted as a matrix, and modified aerogel is added, so that the tensile strength, the flexibility and the wettability to electrolyte of the diaphragm paper are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of diaphragm paper, and in particular to a dry cell diaphragm paper and a preparation method thereof. Background Art

[0002] Dry cell batteries, also known as disposable batteries, are mainly composed of positive electrodes, negative electrodes, electrolytes, separators and shells. Among them, the separator is usually made of paper or plastic. Battery separator paper is the separator material that separates the positive and negative electrodes in the battery. Its main function is to prevent the positive and negative electrodes in the battery from directly contacting and short-circuiting, and to allow ions in the electrolyte to pass freely between the positive and negative electrodes while electrons cannot pass freely. Among the various parts that make up the battery, the separator material plays a pivotal role, and its quality directly affects the battery performance.

[0003] At present, the diaphragm paper on the market is mainly made of polyethylene and polypropylene, but the porosity, liquid absorption and specific surface energy of the stretched film made of polyolefin are low, the affinity for electrolyte is poor, and the dimensional stability is poor, which can easily cause the positive and negative electrodes of the battery to contact and short-circuit. A large amount of heat is generated instantly, causing the battery to catch fire and explode, affecting the safety of the battery. In addition, the diaphragm paper also needs to be insulated to ensure that the battery can be protected by the automatic shutdown mechanism of the diaphragm under abnormal conditions, preventing short circuits and overheating, thereby improving the safety performance of the battery. Therefore, researchers need to develop a diaphragm paper with high porosity, high alkali absorption rate, good wettability, excellent tensile strength and good thermal insulation performance. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a dry cell separator paper and a preparation method thereof.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] A dry cell separator paper, comprising a composite fiber paper and a reinforcing slurry coated on the surface of the composite fiber paper;

[0007] The reinforcing slurry is obtained by mixing and stirring 2-5 parts of insulating filler, 25-35 parts of polyacrylic acid emulsion and 50-80 parts of deionized water;

[0008] The insulating filler is prepared by the following steps:

[0009] Disperse polyvinyl pyrrolidone in ethanol, add xylene and mix evenly, and divide into two equal parts, respectively recorded as solution A1 and solution A2; add silicon carbide nano whiskers to solution A1 and disperse evenly to obtain solution B; add aluminum nitrate to solution A2 and mix evenly to obtain solution C; mix solution B and solution C, ultrasonicate for 10-20 minutes, adjust the pH to 7-12, continue to react at 15-35°C for 40-60 minutes, stand and age for 2-3 days, centrifuge, wash, dry, and then calcine at 600-800°C for 1.5-3.5 hours to obtain insulating filler;

[0010] Further, in solution A1 and solution A2, the amount ratio of polyvinyl pyrrolidone, ethanol and xylene is 0.6-1.4 g: 160 mL: 40 mL;

[0011] Furthermore, the concentration of silicon carbide nanowhiskers in solution B is 0.1-0.3 mol / L, and the concentration of aluminum nitrate in solution C is 0.2-0.4 mol / L.

[0012] The preparation method of the composite fiber paper comprises the following steps:

[0013] Step B1: γ-aminopropyltriethoxysilane, ethyl orthosilicate and mercaptopropyltrimethoxysilane are mixed in deionized water, and then ammonia water is added and stirred for 8-12 hours, and then filtered, washed and dried to obtain functionalized silica;

[0014] Step B2: Disperse 5-aminoisophthalic acid in dimethylacetamide, add triethylamine and acryloyl chloride in sequence in an ice-water bath, heat to 40-60°C and react for 3.5-4.5h, then transfer to 10°C deionized water and stir for 10min, filter, wash and dry to obtain an intermediate product;

[0015] Step B3: Disperse the functionalized silica in deionized water, add the intermediate product and triethylamine solution in sequence under nitrogen, adjust the pH to 9.8-10.2, raise the temperature to 75-85° C., react for 6-8 hours, filter, wash and dry to obtain grafted modified silica;

[0016] Step B4: Ultrasonic dispersion of grafted modified silica and sodium alginate in deionized water for 30 minutes, then adding gluconolactone solution under vigorous stirring to form a mixed solution, then pouring the mixed solution into a mold and standing for 30-50 minutes to form a gel, then freeze-drying the gel at -60°C for 48 hours to obtain a modified aerogel;

[0017] Step B5: weigh the raw materials by weight, add 35-45 parts of polypropylene fiber, 20-30 parts of aramid fiber and 10-20 parts of polyester fiber into a pulping machine respectively, add deionized water to disintegrate for 15-25 minutes, and then use a light knife to beat for 50-60 minutes, until the fibers are completely dispersed, to obtain three kinds of fiber slurries;

[0018] Step B6: The three slurries are transferred to a slurry preparation tank, deionized water is added to prepare a mass percentage concentration of 0.3%-0.7%, and then 1-2mL, 0.5-1.5wt% of a dispersant (carboxymethyl cellulose) and 25-35 parts of modified aerogel are added and stirred to form a mixed slurry, and then the mixed slurry is dehydrated, pressed, dried, and hot-pressed on a mesh cloth, and then rolled and cut to obtain a composite fiber paper;

[0019] Further, in step B1, the usage ratio of γ-aminopropyltriethoxysilane, ethyl orthosilicate, mercaptopropyltrimethoxysilane, deionized water and ammonia water is 0.005-0.02 mol: 0.04-0.1 mol: 0.01-0.02 mol: 200 mL: 0.3-0.6 mL;

[0020] Further, in step B2, the usage ratio of 5-aminoisophthalic acid, dimethylacetamide, triethylamine, acryloyl chloride and deionized water is 0.05-0.1 mol: 100 mL: 10-20 mL: 0.05-0.1 mol: 100 mL;

[0021] Further, in step B3, the mass ratio of the functionalized silica, deionized water, the intermediate product and the triethylamine solution is 0.5-1.5:100:1-5:1-3, and the triethylamine solution is prepared by mixing triethylamine and deionized water in a mass ratio of 0.5-1:20;

[0022] Further, in step B4, the amount ratio of grafted modified silica, sodium alginate, deionized water and gluconolactone solution is 0.4-1.2 g: 0.5-1 g: 50 mL: 10 mL, and the gluconolactone solution is prepared by mixing gluconolactone and deionized water in an amount ratio of 0.3-0.6 g: 10 mL;

[0023] Furthermore, in step B5, the mass percentage concentration of each fiber in the three fiber slurries is 0.5%-1.5%.

[0024] A method for preparing a dry cell separator paper comprises the following steps:

[0025] The reinforcing slurry is evenly coated on the surface of the composite fiber paper with a coating thickness of 0.15-0.2 mm, and then dried to obtain the dry cell separator paper.

[0026] Beneficial effects of the present invention:

[0027] The dry cell separator paper prepared by the invention consists of two parts: composite fiber paper and reinforcing slurry coated on the surface of the composite fiber paper. The separator paper has the advantages of excellent strength, high porosity, high alkali absorption rate, good wettability and the like.

[0028] The reinforcing filler in the reinforced slurry is based on silicon carbide whiskers and is formed by aluminum oxide as a coating layer. After being introduced into the slurry and coated on the surface of the composite fiber paper, the tensile strength and chemical stability of the diaphragm paper can be improved. This is because the silicon carbide nanowhiskers can exert their excellent toughness and strength, thereby improving the tensile strength of the diaphragm paper. At the same time, the aluminum oxide coating can utilize its own excellent thermal insulation properties to prevent short circuits and overheating, thereby improving the safety performance of the battery.

[0029] In the composite fiber paper, γ-aminopropyltriethoxysilane, ethyl orthosilicate and mercaptopropyltrimethoxysilane are first used as silicon sources to synthesize functionalized silica containing mercapto and amino groups; then 5-aminoisophthalic acid and acryloyl chloride are reacted to synthesize an intermediate product containing a double bond structure; then the reaction between the mercapto groups in the functionalized silica and the double bonds in the intermediate product is used to synthesize grafted modified silica, and then the grafted modified silica, sodium alginate and gluconolactone are used as raw materials to synthesize modified aerogel; finally, polypropylene fiber, aramid fiber and polyester fiber are used as base fibers, and modified aerogel and dispersant are added to synthesize composite fiber paper. The composite fiber paper uses a composite fiber blended with polypropylene fiber, aramid fiber and polyester fiber as the matrix, among which polypropylene fiber can improve the density and alkali resistance of the dry battery separator paper, which is beneficial to ensure the pore size and chemical stability of the battery separator paper, while the aramid fiber contains a rigid benzene ring structure, has excellent heat resistance and antioxidant properties, can greatly reduce the thermal shrinkage rate of the separator paper at high temperature, avoid the hidden danger of battery fire, and greatly improve safety; the introduction of modified aerogel improves the tensile strength, flexibility and wettability of the separator paper to the electrolyte, this is because sodium alginate and hydrophilic silica are introduced into the modified aerogel, they contain a large number of hydrophilic groups, such as amino, carboxyl, etc., these groups can form a hydrophilic layer on the surface of the fiber paper, thereby improving the wettability to the electrolyte, and the aerogel itself has an excellent pore structure and a lower mass, can improve the porosity of the separator paper, and can also reduce the quantitative of the separator paper. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] Example 1

[0032] The insulating filler is prepared by the following steps:

[0033] 0.6 g of polyvinyl pyrrolidone was dispersed in 160 mL of ethanol, and then 40 mL of xylene was added and mixed evenly, and the mixture was divided into two equal parts, which were respectively recorded as solution A1 and solution A2; 0.01 mol of silicon carbide nanowhiskers was added into 100 mL of solution A1 and dispersed evenly to obtain solution B; 0.02 mol of aluminum nitrate was added into 100 mL of solution A2 and mixed evenly to obtain solution C; solution B and solution C were mixed and ultrasonicated for 10 minutes, and the pH was adjusted to 7, and the reaction was continued at 15°C for 40 minutes, and the mixture was aged for 2 days, centrifuged, washed, dried, and then calcined at 600°C for 1.5 hours to obtain an insulating filler.

[0034] The preparation method of the composite fiber paper comprises the following steps:

[0035] Step B1: 0.005 mol of γ-aminopropyltriethoxysilane, 0.04 mol of ethyl orthosilicate and 0.01 mol of mercaptopropyltrimethoxysilane were mixed in 200 mL of deionized water, and then 0.3 mL of ammonia water was added and stirred for 8 h, filtered, washed and dried to obtain functionalized silica;

[0036] Step B2: Disperse 0.05 mol of 5-aminoisophthalic acid in 100 mL of dimethylacetamide, add 10 mL of triethylamine and 0.05 mol of acryloyl chloride in an ice-water bath, heat to 40°C and react for 3.5 hours, then transfer to 100 mL of 10°C deionized water and stir for 10 minutes, filter, wash and dry to obtain an intermediate product;

[0037] Step B3: 0.5 g of functionalized silica was dispersed in 100 g of deionized water, and 1 g of the intermediate product and 1 g of triethylamine solution were added in sequence under nitrogen conditions, and then the pH was adjusted to 9.8, the temperature was raised to 75° C., the reaction was carried out for 6 h, and the grafted modified silica was obtained by filtering, washing, and drying. The triethylamine solution was prepared by mixing triethylamine and deionized water in a mass ratio of 0.5:20;

[0038] Step B4: 0.4 g of grafted modified silica and 0.5 g of sodium alginate were ultrasonically dispersed in 50 mL of deionized water for 30 min, and then 10 mL of gluconolactone solution was added under vigorous stirring to form a mixed solution, and then the mixed solution was poured into a mold and allowed to stand for 30 min to form a gel, and then the gel was freeze-dried at -60 ° C for 48 h to obtain a modified aerogel, and the gluconolactone solution was prepared by mixing gluconolactone and deionized water in a dosage ratio of 0.3 g:10 mL;

[0039] Step B5: weigh the raw materials by weight, add 35 parts of polypropylene fiber, 20 parts of aramid fiber and 10 parts of polyester fiber into a pulping machine respectively, add deionized water to disintegrate for 15 minutes, and then use a light knife to beat for 50 minutes, until the fibers are completely dispersed, to obtain three kinds of fiber slurries, and the mass percentage concentration of each fiber in the three kinds of fiber slurries is 0.5%;

[0040] Step B6: The three slurries are transferred to a slurry preparation tank, deionized water is added to prepare a mass percentage concentration of 0.3, and then 1 mL, 0.5 wt% of a dispersant (carboxymethyl cellulose) and 25 parts of modified aerogel are added and stirred to form a mixed slurry. The mixed slurry is then dehydrated, pressed, dried, and hot-pressed on a mesh cloth, and then rolled and cut to obtain a composite fiber paper.

[0041] Example 2

[0042] The insulating filler is prepared by the following steps:

[0043] 1 g of polyvinyl pyrrolidone was dispersed in 160 mL of ethanol, and then 40 mL of xylene was added and mixed evenly, and the mixture was divided into two equal parts, which were respectively recorded as solution A1 and solution A2; 0.02 mol of silicon carbide nanowhiskers was added into 100 mL of solution A1 and dispersed evenly to obtain solution B; 0.03 mol of aluminum nitrate was added into 100 mL of solution A2 and mixed evenly to obtain solution C; solution B and solution C were mixed and ultrasonicated for 15 min, and the pH was adjusted to 9, and the reaction was continued at 25°C for 50 min, and the mixture was aged for 2.5 d, centrifuged, washed, dried, and then calcined at 700°C for 2.5 h to obtain an insulating filler.

[0044] The preparation method of the composite fiber paper comprises the following steps:

[0045] Step B1: 0.01 mol of γ-aminopropyltriethoxysilane, 0.07 mol of ethyl orthosilicate and 0.015 mol of mercaptopropyltrimethoxysilane were mixed in 200 mL of deionized water, and then 0.45 mL of ammonia water was added and stirred for 10 hours, filtered, washed and dried to obtain functionalized silica;

[0046] Step B2: Disperse 0.075 mol of 5-aminoisophthalic acid in 100 mL of dimethylacetamide, add 15 mL of triethylamine and 0.075 mol of acryloyl chloride in an ice-water bath, heat to 50°C and react for 4 h, then transfer to 100 mL of 10°C deionized water and stir for 10 min, filter, wash and dry to obtain an intermediate product;

[0047] Step B3: 1 g of functionalized silica was dispersed in 100 g of deionized water, and 3 g of the intermediate product and 2 g of triethylamine solution were added in sequence under nitrogen conditions, and then the pH was adjusted to 10, the temperature was raised to 80° C., the reaction was carried out for 7 h, and the grafted modified silica was obtained by filtering, washing, and drying. The triethylamine solution was prepared by mixing triethylamine and deionized water in a mass ratio of 0.75:20;

[0048] Step B4: 0.8 g of grafted modified silica and 0.75 g of sodium alginate were ultrasonically dispersed in 50 mL of deionized water for 30 min, and then 10 mL of gluconolactone solution was added under vigorous stirring to form a mixed solution, and then the mixed solution was poured into a mold and allowed to stand for 40 min to form a gel, and then the gel was freeze-dried at -60°C for 48 h to obtain a modified aerogel. The gluconolactone solution was prepared by mixing gluconolactone and deionized water in a dosage ratio of 0.45 g:10 mL;

[0049] Step B5: weigh the raw materials by weight, add 40 parts of polypropylene fiber, 25 parts of aramid fiber and 15 parts of polyester fiber into a pulping machine respectively, add deionized water to disintegrate for 20 minutes, and then use a light knife to beat for 55 minutes, until the fibers are completely dispersed, to obtain three kinds of fiber slurries, and the mass percentage concentration of each fiber in the three kinds of fiber slurries is 1%;

[0050] Step B6: The three slurries are transferred to a slurry preparation tank, deionized water is added to prepare a mass percentage concentration of 0.5%, and then 1.5 mL, 1 wt% of a dispersant (carboxymethyl cellulose) and 30 parts of modified aerogel are added and stirred to form a mixed slurry. The mixed slurry is then dehydrated, pressed, dried, and hot-pressed on a mesh cloth, and then rolled and cut to obtain a composite fiber paper.

[0051] Example 3

[0052] The insulating filler is prepared by the following steps:

[0053] 1.4 g of polyvinyl pyrrolidone was dispersed in 160 mL of ethanol, and then 40 mL of xylene was added and mixed evenly, and the mixture was divided into two equal parts, which were respectively recorded as solution A1 and solution A2; 0.03 mol of silicon carbide nanowhiskers was added into 100 mL of solution A1 and dispersed evenly to obtain solution B; 0.04 mol of aluminum nitrate was added into 100 mL of solution A2 and mixed evenly to obtain solution C; solution B and solution C were mixed and ultrasonicated for 20 min, and the pH was adjusted to 12, and the reaction was continued at 35°C for 60 min, and the mixture was aged for 3 d, centrifuged, washed, dried, and then calcined at 800°C for 3.5 h to obtain an insulating filler.

[0054] The preparation method of the composite fiber paper comprises the following steps:

[0055] Step B1: 0.02 mol of γ-aminopropyltriethoxysilane, 0.1 mol of ethyl orthosilicate and 0.02 mol of mercaptopropyltrimethoxysilane were mixed in 200 mL of deionized water, and then 0.6 mL of ammonia water was added and stirred for 12 h, filtered, washed and dried to obtain functionalized silica;

[0056] Step B2: Disperse 0.1 mol of 5-aminoisophthalic acid in 100 mL of dimethylacetamide, add 20 mL of triethylamine and 0.1 mol of acryloyl chloride in an ice-water bath, heat to 60°C and react for 4.5 hours, then transfer to 100 mL of 10°C deionized water and stir for 10 minutes, filter, wash and dry to obtain an intermediate product;

[0057] Step B3: 1.5 g of functionalized silica was dispersed in 100 g of deionized water, and 5 g of the intermediate product and 3 g of triethylamine solution were added in sequence under nitrogen conditions, and then the pH was adjusted to 10.2, the temperature was raised to 85° C., the reaction was carried out for 8 h, and the grafted modified silica was obtained by filtering, washing, and drying. The triethylamine solution was prepared by mixing triethylamine and deionized water in a mass ratio of 1:20;

[0058] Step B4: 1.2 g of grafted modified silica and 1 g of sodium alginate were ultrasonically dispersed in 50 mL of deionized water for 30 min, and then 10 mL of gluconolactone solution was added under vigorous stirring to form a mixed solution, and then the mixed solution was poured into a mold and allowed to stand for 50 min to form a gel, and then the gel was freeze-dried at -60°C for 48 h to obtain a modified aerogel. The gluconolactone solution was prepared by mixing gluconolactone and deionized water in a dosage ratio of 0.6 g:10 mL;

[0059] Step B5: weigh the raw materials by weight, add 45 parts of polypropylene fiber, 30 parts of aramid fiber and 20 parts of polyester fiber into a pulping machine respectively, add deionized water to disintegrate for 25 minutes, and then use a light knife to beat for 60 minutes, until the fibers are completely dispersed, to obtain three kinds of fiber slurries, and the mass percentage concentration of each fiber in the three kinds of fiber slurries is 1.5%;

[0060] Step B6: The three slurries are transferred to a slurry preparation tank, deionized water is added to prepare a mass percentage concentration of 0.7%, and then 2 mL, 1.5 wt% of a dispersant (carboxymethyl cellulose) and 35 parts of modified aerogel are added and stirred to form a mixed slurry. The mixed slurry is then dehydrated, pressed, dried, and hot-pressed on a mesh cloth, and then rolled and cut to obtain a composite fiber paper.

[0061] Example 4

[0062] A dry cell separator paper, comprising the composite fiber paper prepared in Example 1 and a reinforcing slurry coated on the surface of the composite fiber paper;

[0063] The reinforcing slurry is prepared by mixing and stirring 2 parts of the insulating filler prepared in Example 1, 25 parts of polyacrylic acid emulsion and 50 parts of deionized water;

[0064] The preparation method comprises the following steps: uniformly coating the reinforcing slurry on the surface of the composite fiber paper prepared in Example 1 with a coating thickness of 0.15 mm, and drying to obtain a dry cell separator paper.

[0065] Example 5

[0066] A dry cell separator paper, comprising the composite fiber paper prepared in Example 2 and a reinforcing slurry coated on the surface of the composite fiber paper;

[0067] The reinforcing slurry is prepared by mixing and stirring 3.5 parts of the insulating filler prepared in Example 2, 30 parts of polyacrylic acid emulsion and 70 parts of deionized water;

[0068] The preparation method comprises the following steps: uniformly coating the reinforcing slurry on the surface of the composite fiber paper prepared in Example 2 with a coating thickness of 0.17 mm, and drying to obtain dry cell separator paper.

[0069] Example 6

[0070] A dry cell separator paper, comprising the composite fiber paper prepared in Example 3 and a reinforcing slurry coated on the surface of the composite fiber paper;

[0071] The reinforcing slurry is prepared by mixing and stirring 5 parts of the insulating filler prepared in Example 3, 35 parts of polyacrylic acid emulsion and 80 parts of deionized water;

[0072] The preparation method comprises the following steps: uniformly coating the reinforcing slurry on the surface of the composite fiber paper prepared in Example 3 with a coating thickness of 0.2 mm, and drying to obtain a dry cell separator paper.

[0073] Comparative Example 1

[0074] This comparative example is a diaphragm paper, which differs from Example 5 in that aluminum oxide is used instead of the reinforcing filler prepared in Example 2, and the rest is the same.

[0075] Comparative Example 2

[0076] This comparative example is a separator paper, which is different from Example 5 in that the composite fiber paper prepared in Example 2 is replaced by fiber paper, and the rest are the same;

[0077] The fiber paper is prepared by the following steps:

[0078] Step A1: weigh the raw materials by weight, add 45 parts of polypropylene fiber, 30 parts of aramid fiber and 20 parts of polyester fiber into a pulping machine respectively, add deionized water to disintegrate for 25 minutes, and then use a light knife to beat for 60 minutes, until the fibers are completely dispersed, to obtain three kinds of fiber slurries, and the mass percentage concentration of each fiber in the three kinds of fiber slurries is 1.5%;

[0079] Step A2: The three slurries are transferred to a slurry preparation tank, deionized water is added to prepare a mass percentage concentration of 0.7%, and then 2 mL, 1.5 wt% of a dispersant (carboxymethyl cellulose) and 35 parts of modified aerogel are added and stirred to form a mixed slurry. The mixed slurry is then dehydrated, pressed, dried, and hot-pressed on a mesh cloth, and then rolled and cut to obtain fiber paper.

[0080] The performance test of the diaphragm paper prepared in Examples 4-6 and Comparative Examples 1-2 was performed under quasi-constant temperature and humidity conditions of (23±1)°C and relative humidity of (50±2)% for 24 hours:

[0081] Quantitative test: Test in accordance with GB / T 451.2-2002 "Determination of Quantitative Weight of Paper and Paperboard";

[0082] Tensile strength test: GB / T 12914-2018 "Determination of tensile strength of paper and paperboard";

[0083] Porosity test: Use the liquid absorption method to dry the diaphragm paper in an oven for 12 hours to completely remove moisture, then cut a sample with a side length of 20 mm and weigh the mass μ 0 , soak the sample in n-butanol for 6 hours and then take it out. Use filter paper to absorb the excess liquid on the surface and weigh its mass μ, where ρ1 is the density of the dry paper sample and ρ2 is the density of n-butanol. Calculate the porosity = (μ 0 -μ)*ρ1 / (ρ1μ+(ρ1-ρ2)*μ 0 )*100%;

[0084] Alkali absorption rate test: dry the diaphragm paper in an oven for 12 hours to completely remove moisture, cut a sample with a side length of 20 mm, weigh its mass as m1, soak the diaphragm paper in electrolyte for 6 hours and then take it out, wipe off the excess electrolyte on the surface with filter paper, weigh the mass of the sample at this time as m2, and calculate the liquid absorption rate γ = (m2-m1)m1*100%;

[0085] Contact angle test: Use a contact angle meter to drop a drop of electrolyte on the surface of the separator paper and measure the contact angle within 10 seconds to characterize the electrolyte wettability of the separator paper;

[0086] The test results are shown in the following table:

[0087]

[0088]

[0089] As can be seen from the table above, after the quantitative, tensile strength, porosity, alkali absorption rate and contact angle tests of the diaphragm paper prepared by the present invention, the quantitative value is 38.4 g / m 2 -39.2g / m 2 The tensile index is in the range of 35.6N·m / g-36.3N·m / g, the porosity is in the range of 53%-56%, the alkali absorption rate is in the range of 238.3%-252.1%, and the contact angle is in the range of 80.6°-82.1°, indicating that the diaphragm paper has a good application prospect in dry batteries.

[0090] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A dry cell separator paper, characterized in that: It consists of two parts: composite fiber paper and reinforcing slurry coated on the surface of composite fiber paper; The reinforcing slurry is obtained by mixing and stirring 2-5 parts of insulating filler, 25-35 parts of polyacrylic acid emulsion and 50-80 parts of deionized water; The insulating filler is prepared by the following steps: Disperse polyvinyl pyrrolidone in ethanol, add xylene and mix evenly, and divide into two equal parts, respectively recorded as solution A1 and solution A2; add silicon carbide nanowhiskers to solution A1 and disperse evenly to obtain solution B; add aluminum nitrate to solution A2 and mix evenly to obtain solution C; mix solution B and solution C, ultrasonicate for 10-20 minutes, adjust the pH to 7-12, continue to react at 15-35°C for 40-60 minutes, stand and age for 2-3 days, centrifuge, wash, dry, and then calcine at 600-800°C for 1.5-3.5 hours to obtain insulating filler.

2. A dry cell separator paper according to claim 1, characterized in that: In the insulating filler solutions A1 and A2, the dosage ratio of polyvinyl pyrrolidone, ethanol and xylene is 0.6-1.4 g: 160 mL: 40 mL, the concentration of silicon carbide nano whiskers in solution B is 0.1-0.3 mol / L, and the concentration of aluminum nitrate in solution C is 0.2-0.4 mol / L.

3. The dry cell separator paper according to claim 1, characterized in that: The preparation method of the composite fiber paper comprises the following steps: Step B1: γ-aminopropyltriethoxysilane, ethyl orthosilicate and mercaptopropyltrimethoxysilane are mixed in deionized water, and then ammonia water is added and stirred for 8-12 hours, and then filtered, washed and dried to obtain functionalized silica; Step B2: Disperse 5-aminoisophthalic acid in dimethylacetamide, add triethylamine and acryloyl chloride in sequence in an ice-water bath, heat to 40-60°C and react for 3.5-4.5h, then transfer to 10°C deionized water and stir for 10min, filter, wash and dry to obtain an intermediate product; Step B3: Disperse the functionalized silica in deionized water, add the intermediate product and triethylamine solution in sequence under nitrogen, adjust the pH to 9.8-10.2, raise the temperature to 75-85° C., react for 6-8 hours, filter, wash and dry to obtain grafted modified silica; Step B4: Ultrasonic dispersion of grafted modified silica and sodium alginate in deionized water for 30 minutes, then adding gluconolactone solution under vigorous stirring to form a mixed solution, then pouring the mixed solution into a mold and standing for 30-50 minutes to form a gel, then freeze-drying the gel at -60°C for 48 hours to obtain a modified aerogel; Step B5: weigh the raw materials by weight, add 35-45 parts of polypropylene fiber, 20-30 parts of aramid fiber and 10-20 parts of polyester fiber into a pulping machine respectively, add deionized water to disintegrate for 15-25 minutes, and then use a light knife to beat for 50-60 minutes, until the fibers are completely dispersed, to obtain three kinds of fiber slurries; Step B6: Transfer the three slurries to a slurry preparation tank, add deionized water to prepare a mass percentage concentration of 0.3%-0.7%, then add 1-2mL, 0.5-1.5wt% of a dispersant and 25-35 parts of modified aerogel, stir and mix evenly to form a mixed slurry, and then dehydrate the mixed slurry on a mesh, press, dry, and hot-press it, and then roll it and cut it to obtain a composite fiber paper.

4. A dry cell separator paper according to claim 3, characterized in that: In step B1, the usage ratio of γ-aminopropyltriethoxysilane, ethyl orthosilicate, mercaptopropyltrimethoxysilane, deionized water and ammonia water is 0.005-0.02 mol: 0.04-0.1 mol: 0.01-0.02 mol: 200 mL: 0.3-0.6 mL.

5. The dry cell separator paper according to claim 3, characterized in that: In step B2, the usage ratio of 5-aminoisophthalic acid, dimethylacetamide, triethylamine, acryloyl chloride and deionized water is 0.05-0.1 mol: 100 mL: 10-20 mL: 0.05-0.1 mol: 100 mL.

6. The dry cell separator paper according to claim 3, characterized in that: In step B3, the mass ratio of the functionalized silica, deionized water, the intermediate product and the triethylamine solution is 0.5-1.5:100:1-5:1-3, and the triethylamine solution is prepared by mixing triethylamine and deionized water in a mass ratio of 0.5-1:

20.

7. The dry cell separator paper according to claim 3, characterized in that: In step B4, the amount ratio of grafted modified silica, sodium alginate, deionized water and gluconolactone solution is 0.4-1.2 g: 0.5-1 g: 50 mL: 10 mL, and the gluconolactone solution is prepared by mixing gluconolactone and deionized water in an amount ratio of 0.3-0.6 g: 10 mL.

8. The dry cell separator paper according to claim 3, characterized in that: In step B5, the mass percentage concentration of each fiber in the three fiber slurries is 0.5%-1.5%.

9. A method for preparing the dry cell separator paper according to any one of claims 1 to 8, characterized in that: The following steps are involved: The reinforcing slurry is evenly coated on the surface of the composite fiber paper with a coating thickness of 0.15-0.2 mm, and then dried to obtain the dry cell separator paper.

Citation Information

Patent Citations

  • Coating for power lithium battery diaphragm, power lithium battery diaphragm and preparation thereof

    CN102433745A

  • Method for preparing alkaline battery diaphragm paper

    CN106592322A

  • Lithium battery diaphragm ceramic slurry with high temperature resistance and preparation method thereof

    CN109320134A

  • Lithium ion battery separator and preparation method thereof

    CN109428033A